Self-cleaning coating with smooth surface as well as preparation and application of self-cleaning coating

By synthesizing amino-terminal hyperbranched silicones and forming their coatings, the problem of complex preparation of conventional hyperbranched silicones and poor durability of hydrophobic coatings is solved, and efficient and environmentally friendly hydrophobic and durable coatings are achieved, which are suitable for glass and other fields.

CN119798668AActive Publication Date: 2025-04-11JIANGNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411821313.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The preparation method of conventional hyperbranched silicones has problems such as complex process, gel problems, and mass loss; it is difficult to take into account both convenient operation, low cost, hydrophobic, durability and environmental protection; Hyperbranched polysiloxanes are not found to be used in glass to improve hydrophobic and durability.

Method used

The amino-terminal hyperbranched silicone is synthesized by hydrolysis condensation reaction and dispersed in anhydrous ethanol to form a precursor, coated on a smooth surface and cross-linked to form a self-cleaning coating. The amino-terminal hyperbranched polysiloxane-modified particle coating can be formed by adding nanoparticles.

Benefits of technology

It realizes a smooth surface self-cleaning coating with simple preparation and good hydrophobic and durable properties, and is not modified with fluorine, making it environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798668A_ABST
    Figure CN119798668A_ABST
Patent Text Reader

Abstract

The invention discloses a self-cleaning coating with a smooth surface as well as preparation and application of the self-cleaning coating, and belongs to the technical field of self-cleaning. The preparation method comprises the following steps: by taking KH-792 and methoxytrimethylsilane as raw materials, synthesizing amino-terminated hyperbranched siloxane through hydrolytic condensation reaction; dispersing amino-terminated hyperbranched siloxane in absolute ethyl alcohol to form an amino-terminated hyperbranched siloxane precursor, coating the smooth surface with the amino-terminated hyperbranched siloxane precursor, and performing cross-linking curing to form the self-cleaning coating with the smooth surface. In addition, the coating system can also form an amino-terminated hyperbranched polysiloxane-modified particle coating by adding nano particles. The method for preparing the amino-terminated hyperbranched siloxane is simple; when being used on a smooth surface, the hydrophobic self-cleaning coating can be formed stably; in addition, the amino-terminated hyperbranched polysiloxane-modified particle coating is hydrophobic and better in durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a self-cleaning coating with a smooth surface and a preparation method and application thereof, belonging to the technical field of self-cleaning. Background Art

[0002] Hyperbranched siloxane is a polymer with Si-O-Si bond as the main chain and organic groups as side groups. Since the Si-O-Si bond is long, the bond angle is large, and it is easy to rotate, the intermolecular force is small, and the molecule is highly flexible. Hyperbranched siloxane has the advantages of low glass transition temperature (Tg), surface tension, small solubility parameters and dielectric constant; it is often used in the fields of electronics, resin modification, construction, coatings, etc. However, the preparation method of conventional hyperbranched siloxane has problems such as complex process (for example: the hydrosilylation method requires the use of platinum catalyst), gel problem (siloxane is prone to gel in the hydrolysis condensation method), quality loss (most of the polysiloxanes prepared by the hydrolysis condensation method will lose mass due to the volatilization of a large number of water molecules during hydroxyl condensation, resulting in strong shrinkage and possible cracking).

[0003] The hydrophobic surface has excellent self-cleaning properties. Applying the hydrophobic surface to glass materials can make the glass surface have a self-cleaning effect, thereby reducing the cleaning cost of the glass. In practical applications, the hydrophobic coating not only needs to have good hydrophobicity, but also needs to have good durability. Therefore, it is of great practical significance to prepare a durable, hydrophobic glass coating so that it can be well applied to the fields of automotive glass, architectural glass, and solar photovoltaic glass.

[0004] Hydrophobic coatings are usually prepared by combining surface micro-nano composite structures with low surface energy materials. At present, the preparation methods of hydrophobic coatings on glass include template method, sol-gel method, spraying method, chemical deposition method, electrochemical deposition method, laser etching method, chemical etching method, nanoparticle filling method, etc.; among them, the template method is to use a low surface energy template to replicate a rough structure, and then remove the template. Although this method is easy to handle and has low cost, it is difficult to remove the template and it is difficult to achieve the construction of large-scale super-hydrophobic coatings (Wang Yifan, Xu Junhuang, Li Li, et al. Research Progress on Super-hydrophobic Coatings and Their Functionalization [J]. Coatings Industry, 2024(002):054.); the sol-gel method is to prepare a uniform sol, convert the sol into a gel, remove the solvent in the gel, and further solidify it to form a hydrophobic material with a specific structure. Although this method is easy to operate and easy to control, it takes a long time to process and is difficult to manufacture. Easy to shrink; the spraying method is to prepare the coating solution and then spray and dry it. Although this method is low-cost and has a wide range of applications, it has poor adhesion (Yang Likai, Wu Linsen, Yang Xu, et al. Research Progress on Preparation, Performance and Application of Superhydrophobic Coatings [J]. Journal of Composite Materials, 2024, 41(8): 3950-3967. DOI: 10.13801 / j.cnki.fhclxb.20240314.003); the chemical deposition method is to deposit low surface energy nanoparticles on the surface of the substrate through chemical reaction to form a high-performance film. Although this method is easy to handle and has strong acid and alkali resistance, the deposition rate is slow and it is likely to cause air pollution; the laser etching method is to use high-energy laser to ablate the substrate to change the surface roughness of the substrate. Although it is easy to control, it is costly. It can be seen that the deposition method and the etching method can well control the rough micro-nano structure of the glass surface. However, these two methods have high requirements on the preparation equipment, resulting in high preparation costs and poor durability of the prepared transparent hydrophobic glass, so it is difficult to apply to large-scale production; while the spraying method has low equipment requirements and high material utilization rate, and can be well applied to large-scale production, but due to the lack of effective control means for the construction of the rough micro-nano structure on the glass surface during the preparation process, its durability is poor.

[0005] In addition, in order to achieve better hydrophobic effects, hydrophobic surface structures are often modified by adding low surface energy fluorides or using organic fluorine, which causes certain environmental problems. Summary of the invention

[0006] [Technical issues]

[0007] Conventional hyperbranched siloxane preparation methods have problems such as complex process, gel problem, and quality loss;

[0008] It is difficult for hydrophobic coatings to simultaneously take into account the convenience of operation, low cost, hydrophobicity, durability, and environmental protection;

[0009] No literature has been found that mentions the use of hyperbranched polysiloxane (HBPSi) in glass to improve its hydrophobicity and durability.

[0010] [Technical solution]

[0011] In order to solve the above problems, the present invention uses KH-792 and methoxytrimethylsilane as raw materials, and synthesizes amino-terminated hyperbranched siloxane through hydrolysis and condensation reaction; then the amino-terminated hyperbranched siloxane is dispersed in anhydrous ethanol to form an amino-terminated hyperbranched siloxane precursor, which is coated on a smooth surface, cross-linked and cured to form a self-cleaning coating on a smooth surface. In addition, the coating system can also form an amino-terminated hyperbranched polysiloxane-modified particle coating by adding nanoparticles. The method for preparing amino-terminated hyperbranched siloxane of the present invention is simple; and it can form a stable hydrophobic self-cleaning coating for a smooth surface; in addition, the amino-terminated hyperbranched polysiloxane-modified particle coating has better hydrophobicity and durability.

[0012] The first object of the present invention is to provide a method for preparing amino-terminated hyperbranched siloxanes, comprising the steps of:

[0013] Mix KH-792, methoxytrimethylsilane, anhydrous ethanol and water in a molar ratio of 0.8-1.2:0.8-1.2:2.4-2.8:2, and perform a hydrolysis condensation reaction at 45-53°C for 20-40 minutes;

[0014] Afterwards, the pH is adjusted to 1-3, and the reaction is continued at 55-60° C. and 350-550 rpm with stirring for 4-6 hours. The mixture is cooled, and by-products are removed to obtain a viscous liquid, namely, amino-terminated hyperbranched siloxane.

[0015] In one embodiment of the present invention, the full name of KH-792 is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and the CAS number is 1760-24-3.

[0016] In one embodiment of the present invention, the water is deionized water.

[0017] In one embodiment of the present invention, the molar ratio of KH-792, methoxytrimethylsilane, anhydrous ethanol and water is 1:1:2.6:2.

[0018] In one embodiment of the present invention, the hydrolysis condensation reaction is carried out at 50° C. for 30 min.

[0019] In one embodiment of the present invention, the stirring reaction is carried out at 55° C. and 450 rpm for 5 h.

[0020] In one embodiment of the present invention, the pH is adjusted by using a hydrochloric acid aqueous solution, and the concentration of the hydrochloric acid aqueous solution is 0.1-2 mol / L.

[0021] In one embodiment of the present invention, the by-products are removed by evaporating under reduced pressure at 55-65° C. for 2-4 hours.

[0022] The second object of the present invention is the amino-terminated hyperbranched siloxane prepared by the method of the present invention.

[0023] A third object of the present invention is to provide a method for preparing a self-cleaning coating on a smooth surface, comprising the steps of:

[0024] The amino-terminated hyperbranched siloxane is dispersed in anhydrous ethanol, and then ethylene glycol diglycidyl ether is added and mixed uniformly to obtain a uniform and transparent precursor; wherein the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in the ethylene glycol diglycidyl ether is 1:0-2;

[0025] The precursor is then coated on a smooth surface, cross-linked and cured to obtain a self-cleaning coating.

[0026] In one embodiment of the present invention, the mass ratio of amino-terminated hyperbranched siloxane to anhydrous ethanol is 20-40:100.

[0027] In one embodiment of the present invention, the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in ethylene glycol diglycidyl ether is 1:0.5-2.

[0028] In one embodiment of the present invention, the mixing is performed by stirring at 15-40 (room temperature) and 250-350 rpm for 5-10 min.

[0029] In one embodiment of the present invention, the smooth surface is one of a glass surface, a stainless steel surface, a metal copper surface, and a bakelite surface.

[0030] In one embodiment of the present invention, the cross-linking and curing is cross-linking and curing at 90-100° C. for 0.5-2 h to allow ethanol to evaporate.

[0031] In one embodiment of the present invention, the thickness of the self-cleaning coating on the smooth surface is 5-15 μm.

[0032] The fourth object of the present invention is a self-cleaning coating with a smooth surface prepared by the method of the present invention.

[0033] A fifth object of the present invention is to provide a method for preparing an amino-terminated hyperbranched polysiloxane-modified particle coating, comprising the steps of:

[0034] (1) Preparation of modified particles:

[0035] Add nanoparticles into the ethanol solution and disperse them evenly to obtain component A; wherein the nanoparticles are one or two of SiO2 and Al2O3;

[0036] Add a modifying agent, a cross-linking agent, and a catalyst into anhydrous ethanol and mix them evenly to obtain component B; wherein the modifying agent is one or two of KH560 and hexadecyltrimethoxysilane HDTMS;

[0037] The components A and B are mixed and reacted, and after the reaction is completed, they are centrifuged and dried to obtain modified particles;

[0038] (2) Preparation of amino-terminated hyperbranched polysiloxane-modified particle coating:

[0039] The amino-terminated hyperbranched siloxane is dispersed in anhydrous ethanol, and then ethylene glycol diglycidyl ether is added and mixed evenly to obtain a uniform and transparent precursor; wherein the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in the ethylene glycol diglycidyl ether is 1:0.5-2;

[0040] Afterwards, modified particles are added to the precursor to obtain a precursor containing the modified particles;

[0041] Finally, the precursor containing the modified particles is coated on the smooth surface, cross-linked and cured to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

[0042] In one embodiment of the present invention, the volume ratio of anhydrous ethanol to water in the ethanol solution of step (1) is 85-95:5-15.

[0043] In one embodiment of the present invention, the particle size of the nanoparticles in step (1) is 20-40 μm.

[0044] In one embodiment of the present invention, the ratio of the nanoparticles to the ethanol solution in step (1) is 4-6 g:100 mL.

[0045] In one embodiment of the present invention, the uniform dispersion in step (1) is ultrasonic dispersion.

[0046] In one embodiment of the present invention, in step (1), the volume ratio of anhydrous ethanol, modifying agent, cross-linking agent and catalyst is 20:2-4:0.5-1.5:0.4-0.6.

[0047] In one embodiment of the present invention, in step (1), the crosslinking agent is tetraethyl orthosilicate (TEOS), and the catalyst is an aqueous ammonia solution with a purity of 25-28%, GR.

[0048] In one embodiment of the present invention, the uniform mixing in step (1) is ultrasonic mixing.

[0049] In one embodiment of the present invention, the reaction in step (1) is stirred at 15-40°C (room temperature) and 600-800 rpm for 3-5 hours.

[0050] In one embodiment of the present invention, the centrifugation in step (1) is performed at 6000-10000 rpm.

[0051] In one embodiment of the present invention, the drying in step (1) is performed at 90-110° C. for 2-4 hours.

[0052] In one embodiment of the present invention, in step (2), the mass ratio of amino-terminated hyperbranched siloxane to anhydrous ethanol is 20-40:100.

[0053] In one embodiment of the present invention, in step (2), the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in ethylene glycol diglycidyl ether is 1:0.5-2.

[0054] In one embodiment of the present invention, the uniform mixing in step (2) is performed by stirring at 15-40° C. (room temperature) and 350-550 rpm for 5-10 min.

[0055] In one embodiment of the present invention, the mass ratio of the precursor to the modified particles in step (2) is 100:5-15.

[0056] In one embodiment of the present invention, the smooth surface in step (2) is one of a glass surface, a stainless steel surface, a metal copper surface, and a bakelite surface.

[0057] In one embodiment of the present invention, the cross-linking and curing in step (2) is cross-linking and curing at 90-100° C. for 0.5-2 h to allow ethanol to evaporate.

[0058] In one embodiment of the present invention, the thickness of the amino-terminated hyperbranched polysiloxane-modified particle coating on the smooth surface in step (2) is 5-15 μm.

[0059] The sixth object of the present invention is the amino-terminated hyperbranched polysiloxane-modified particle coating prepared by the method described in the present invention.

[0060] The seventh objective of the present invention is the application of the self-cleaning coating with smooth surface, amino-terminated hyperbranched siloxane, amino-terminated hyperbranched polysiloxane-modified particle coating described in the present invention in the fields of automotive glass, architectural glass or solar photovoltaic glass.

[0061] The eighth object of the present invention is to provide a method for improving the mechanical stability and aging resistance of a smooth self-cleaning surface, which uses the self-cleaning coating of the smooth surface, amino-terminated hyperbranched siloxane or amino-terminated hyperbranched polysiloxane-modified particle coating described in the present invention.

[0062] The ninth object of the present invention is to provide a solar photovoltaic glass, which adopts the self-cleaning coating with a smooth surface, amino-terminated hyperbranched siloxane or amino-terminated hyperbranched polysiloxane-modified particle coating described in the present invention.

[0063] [Beneficial Effects]

[0064] (1) The method for preparing hyperbranched siloxane of the present invention is simple;

[0065] (2) The present invention introduces amino groups when synthesizing hyperbranched siloxane, thereby enhancing the reactivity of the system and the durability and stability of the coating;

[0066] (3) The self-cleaning coating with a smooth surface prepared by the present invention has good hydrophobicity and durability;

[0067] (4) The present invention has good compatibility with epoxy group-modified particles;

[0068] (5) The amino-terminated hyperbranched polysiloxane-modified particle coating prepared by the present invention has good hydrophobicity and durability;

[0069] (6) The present invention does not use fluorine for modification and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 This is the infrared spectrum of the amino-terminated hyperbranched siloxane prepared in Example 1.

[0071] Figure 2 This is the silicon nuclear magnetic resonance spectrum of the amino-terminated hyperbranched siloxane prepared in Example 1.

[0072] Figure 3 This is the shear strength-displacement diagram of the amino-terminated hyperbranched siloxane prepared in Example 1 on glass.

[0073] Figure 4 The shear adhesion strength of the amino-terminated hyperbranched siloxane prepared in Example 1 on different substrates.

[0074] Figure 5 This is the contact angle picture of Example 2 (115.2°).

[0075] Figure 6 This is the contact angle image (108.5°) of Example 2 after 60 peeling tests. DETAILED DESCRIPTION

[0076] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0077] Test method:

[0078] 1. Contact angle test:

[0079] The static water contact angle (WCA) was measured using a contact angle meter (Kruss DSA25, Germany) with a water drop size of 5 μL.

[0080] 2. Aging resistance test:

[0081] The “double 85” experiment is used to simulate the aging resistance test of the coating.

[0082] The "double 85 experiment" usually refers to an accelerated aging test of materials under the conditions of an ambient temperature of 85°C and a relative humidity of 85%.

[0083] 3. Hardness test:

[0084] The pencil hardness of the coating surface is evaluated by ASTM D336. The higher the hardness, the stronger the coating's ability to resist scratches, which also indirectly reflects the coating's wear resistance.

[0085] 4. Mechanical stability test:

[0086] Tape peel (adhesion) testing was performed using high tack tape.

[0087] Among them, the test standard is in accordance with ASTM D3359-09 ε2 The standard method B was used. Generally, the surface-coated sample was pressed with 3M600 transparent tape (purchased from Taobao), and a 1.0 kg weight was placed on the tape to ensure complete adhesion of the tape.

[0088] The acid resistance test was carried out by immersing in a hydrochloric acid solution with a pH of 1.

[0089] 5. Shear adhesion performance test:

[0090] The adhesion performance test was conducted by shear adhesion test according to ASTM F2255 standard, the test substrate specification was 100mm*25mm*3mm, and the test was conducted at a rate of 20mm / min using the 5967X desktop double-column tester from Instron, USA. Raw materials used in the examples:

[0091] Slide: glass, 76 mm × 15 mm, 1-1.2 mm thick, rectangular; purchased from Taobao;

[0092] KH-792: N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, CAS number 1760-24-3; purchased from Titan Technology Exploration Platform;

[0093] Methoxytrimethylsilane: 95%; purchased from Titan Technology Exploration Platform;

[0094] Ethylene glycol diglycidyl ether: AR; purchased from Titan Technology Exploration Platform;

[0095] SiO2: particle size 20 nm, model R972, purchased from Shandong Yousuo Chemical Technology Co., Ltd.;

[0096] Al2O3: particle size 20 nm, purchased from Suzhou Great Pharmaceutical Technology Co., Ltd.;

[0097] KH560: γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 98%, BR, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0098] HDTMS: hexadecyltrimethoxysilane, 97%, purchased from Titan Technology Exploration Platform;

[0099] Tetraethyl orthosilicate: CAS 78-10-4, 95%, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0100] Ammonia solution; purity 25-28%, GR, purchased from Shanghai Myrrel Biochemical Technology Co., Ltd.

[0101] The glass slides used in the examples and comparative examples were all pre-treated, specifically, the surfaces of the glass slides were wiped with anhydrous ethanol and dried, in order to remove stains on the surfaces.

[0102] Example 1

[0103] A method for preparing amino-terminated hyperbranched siloxane comprises the following steps:

[0104] KH-792, methoxytrimethylsilane, anhydrous ethanol and water were mixed in a flask at a molar ratio of 1:1:2.6:2, and a hydrolysis condensation reaction was carried out at 50°C for 30 min;

[0105] Afterwards, 0.1 mol / L aqueous hydrochloric acid solution was added to adjust the pH of the solution to 2, and the reaction was continued to be stirred at 55°C and 450 rpm for 5 hours; after the mixture was cooled to room temperature, it was evaporated under reduced pressure at 60°C for 3 hours to remove by-products to obtain a colorless, transparent, viscous liquid, namely, amino-terminated hyperbranched siloxane (HBPSi-NH2).

[0106] The obtained amino-terminated hyperbranched siloxane was subjected to performance testing, and the test results are as follows:

[0107] Figure 1 This is the infrared spectrum of the amino-terminated hyperbranched siloxane prepared in Example 1. Figure 1 It can be seen that the spectrum shows that -NH2 and -OH are at 3434cm -1 Stretching vibration at 1616cm -1 The peak at 1008-1060cm is the bending vibration of -NH2. -1 The absorption peak at 885 cm is attributed to the Si-O-Si bond. The asymmetric stretching vibration peak of Si-OC appears at 885 cm -1 About 935cm -1 The nearby peak is the asymmetric stretching vibration peak of Si-C, 1320 cm -1 The peaks near can be attributed to the deformation stretching vibration of Si-C. The stretching vibration peak of -CH2 appears at 2800-3050cm -1 The appearance of the above characteristic peaks indicates that the amino-terminated hyperbranched siloxane was successfully prepared.

[0108] Figure 2 This is the NMR silicon spectrum of the amino-terminated hyperbranched siloxane prepared in Example 1. Figure 2 It can be seen that the spectrum is divided into three peaks, representing the terminal unit, the linear unit and the tree-like unit, respectively, which indicates the generation of the branched structure of the amino-terminated hyperbranched siloxane, and it can be shown that the amino-terminated hyperbranched siloxane was successfully prepared.

[0109] Example 2

[0110] A method for preparing a self-cleaning coating with a smooth surface comprises the following steps:

[0111] The amino-terminated hyperbranched siloxane prepared in Example 1 was dispersed in anhydrous ethanol, and ethylene glycol diglycidyl ether was added, and stirred at 25° C. (room temperature) and 300 rpm for 5 min to obtain a uniform and transparent precursor:

[0112] The precursor was coated on the surface of a glass slide and placed in an oven at 100°C for 1 hour for cross-linking and curing to evaporate the ethanol, thereby obtaining a self-cleaning coating for use in self-cleaning coating testing;

[0113] The precursor was coated on the surface of a glass slide, and then another glass slide was pressed on the adhesion area, a force of 2N was applied, and the product was placed in an oven at 100°C for 1h to cross-link and cure to evaporate the ethanol, which was used for shear adhesion strength test;

[0114] Wherein, the mass ratio of amino-terminated hyperbranched siloxane to anhydrous ethanol is 30:100;

[0115] The molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in ethylene glycol diglycidyl ether is 1:2;

[0116] In the self-cleaning coating test, the precursor was coated on the surface of the glass slide by a tetrahedral wet film maker (SZQ-4), and the coating thickness was controlled at 10 μm (± 0.01 μm);

[0117] The coating thickness was controlled at 10 μm (± 0.01 μm) in the shear adhesion strength test.

[0118] Comparative Example 1

[0119] The glass slide in Example 2 was changed to a copper sheet (Copper), and the other shear adhesion strength tests were kept consistent with those in Example 2.

[0120] Comparative Example 2

[0121] The glass slide in Example 2 was adjusted to an aluminum sheet, and the other shear adhesion strength tests were kept consistent with those in Example 2.

[0122] Comparative Example 3

[0123] The glass slide in Example 2 was changed to a wood chip (Wood), and the other shear adhesion strength tests were kept consistent with those in Example 2.

[0124] Comparative Example 4

[0125] The glass slide in Example 2 was adjusted to a PET plastic sheet (PET), and the other shear adhesion strength tests were kept consistent with those in Example 2.

[0126] The obtained coating was subjected to performance test, and the test results are as follows:

[0127] Table 1 Changes in contact angle of self-cleaning coating under different stripping cycles

[0128] Stripping cycle Contact angle / ° 10 115.2 20 113.0 30 111.8 40 111.3 60 108.5

[0129] It can be seen from Table 1 that after 40 peeling cycles, the water contact angle decreased by about 4°, and still maintained good hydrophobicity; after 60 peeling cycles, the water contact angle decreased by about 6.5°, and still maintained good hydrophobicity.

[0130] Table 2 Comparison of the self-cleaning coating of Example 2 and other commercially available coatings

[0131] name Contact angle / ° Self-cleaning coating of Example 2 115.2 Room temperature curing oily fluorocarbon resin JF-2X 98.3 Plastic self-cleaning anti-fouling nano coating agent C1503 95.3 Fluorinated epoxy resin FEPOX-428 100.5 Heptafluorobutyric acid / perfluoropolyether modified epoxy resin 93.0 1H,1H,2H,2H-Perfluorooctyltriethyloxysilane modified MTQ / branched silicone resin 112.1

[0132] It can be seen from Table 2 that the self-cleaning coating of Example 2 does not need to be further modified by adding organic fluorine, and can reach a contact angle of 115.2° after cross-linking and curing, which is far higher than the contact angle of commercially available reagents and resins for self-cleaning coatings, and slightly better than that of fluorine-modified resins, and has good environmental friendliness.

[0133] Table 3 Comparison of the self-cleaning coating of Example 2 and other commercially available coatings

[0134] name Contact angle under normal conditions / ° "Double 85" contact angle after one week / ° Self-cleaning coating of Example 2 115.2 113.0 Room temperature curing oily fluorocarbon resin JF-2X 98.3 98.0 Plastic self-cleaning anti-fouling nano coating agent C1503 95.3 85.2 Fluorinated epoxy resin FEPOX-428 100.5 100.2

[0135] It can be seen from Table 3 that after one week of the "Double 85" test, the self-cleaning coating of Example 2 did not foam, fall off or change color, and the contact angle only slightly decreased; the stability was comparable to that of fluorocarbon resin and epoxy resin, and was significantly better than the commercially available self-cleaning coating reagents. Therefore, it is shown that the self-cleaning coating of Example 2 has good chemical stability.

[0136] Table 4 Comparison of the self-cleaning coating of Example 2 and other commercially available coatings

[0137] name Pencil hardness Self-cleaning coating of Example 2 8H Room temperature curing oily fluorocarbon resin JF-2X 6H Plastic self-cleaning anti-fouling nano coating agent C1503 6H Fluorinated epoxy resin FEPOX-428 8H 1H,1H,2H,2H-Perfluorooctyltriethyloxysilane modified MTQ / branched silicone resin 8H

[0138] It can be seen from Table 4 that the pencil hardness of the self-cleaning coating of Example 2 is comparable to the hardness of the epoxy resin, which proves that the self-cleaning coating of Example 2 has higher hardness and better wear resistance.

[0139] The adhesion performance test results of the coatings prepared in Example 2 and Comparative Examples 1-4 are as follows: Figure 3 and Figure 4 .from Figure 3 and Figure 4 It can be seen that the shear adhesion strength on the glass surface can reach 3.6 MPa, and among various substrates, the adhesion performance to glass is the best, which proves that amino-terminated hyperbranched siloxane has strong and tough properties on the glass substrate.

[0140] Example 3

[0141] The molar ratios of the amino group in the amino-terminated hyperbranched siloxane and the epoxy group in ethylene glycol diglycidyl ether in Example 2 were adjusted to 1:0, 1:0.5, and 1:1, and the other ratios were kept the same as in Example 2 to obtain a self-cleaning coating.

[0142] The obtained self-cleaning coating was subjected to performance testing, and the test results are as follows:

[0143] Table 5

[0144] Molar ratio of amino groups to epoxy groups in ethylene glycol diglycidyl ether Contact angle / ° 1:0 118.5 1:0.5 113.2 1:1 106.5 1:2 (Example 2) 115.2

[0145] It can be seen from Table 5 that when ethylene glycol diglycidyl ether is not added, the contact angle of the self-cleaning coating is the highest, which is 118.5°. However, since pure amino-terminated hyperbranched siloxane has the problems of long curing time and high curing temperature, the introduction of ethylene glycol diglycidyl ether can solve the above problems, and the cross-linking density increases after cross-linking curing, and the comprehensive stability of the coating is enhanced; therefore, the molar ratio of amino group to epoxy group in ethylene glycol diglycidyl ether is selected to be 1:2.

[0146] Example 4

[0147] A method for preparing an amino-terminated hyperbranched polysiloxane-modified particle coating comprises the following steps:

[0148] (1) Preparation of modified particles:

[0149] 5 g SiO2 (20 nm) was added to a mixed solution of 90 mL anhydrous ethanol and 10 mL deionized water, and a uniform component A was formed after ultrasonic dispersion;

[0150] Add 3 mL of modification reagent HDTMS, 1 mL of cross-linking agent tetraethyl orthosilicate (TEOS), and 0.5 mL of catalyst ammonia solution into 20 mL of anhydrous ethanol, and disperse by ultrasonication to form a uniform B component;

[0151] After the components A and B are mixed, they are stirred at 25°C (room temperature) and 600 rpm for 4 hours to allow the modification reagent after silane condensation and hydrolysis to combine with the nanoparticles and complete the modification. After the stirring is completed, the mixture is centrifuged at a speed of 8000 rpm and dried at 100°C for 3 hours to obtain modified particles;

[0152] (2) Preparation of amino-terminated hyperbranched polysiloxane-modified particle coating:

[0153] The amino-terminated hyperbranched siloxane prepared in Example 1 was dispersed in anhydrous ethanol, and then ethylene glycol diglycidyl ether was added, and stirred at 25° C. (room temperature) and 600 rpm for 5 minutes to obtain a uniform and transparent precursor; then, the modified particles were quickly added to the precursor, and ultrasonic dispersion was performed for 5 minutes to obtain a precursor containing modified particles; finally, the precursor containing modified particles was coated on the surface of a glass slide, and placed in an oven at 100° C. for cross-linking and curing for 1 hour to evaporate the ethanol, thereby obtaining an amino-terminated hyperbranched polysiloxane-modified particle coating;

[0154] Wherein, the mass ratio of amino-terminated hyperbranched siloxane to anhydrous ethanol is 30:100;

[0155] The molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in ethylene glycol diglycidyl ether is 1:2;

[0156] The mass ratio of precursor and modified particles was 100:10;

[0157] The precursor containing modified particles was coated on the surface of the glass plate by a tetrahedral wet film maker (SZQ-4), and the coating thickness was controlled at 10 μm (± 0.01 μm).

[0158] Example 5

[0159] The SiO2 in Example 4 was adjusted to Al2O3 (20 nm), and the other parameters were kept consistent with Example 4 to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

[0160] Example 6

[0161] The SiO2 in Example 4 was adjusted to Al2O3 (20 nm), and the HDTMS was adjusted to KH560, and the other conditions were kept consistent with Example 4 to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

[0162] Example 7

[0163] The HDTMS in Example 4 was adjusted to KH560, and the other components were kept consistent with Example 4 to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

[0164] The obtained amino-terminated hyperbranched polysiloxane-modified particle coating was subjected to performance testing, and the test results are as follows:

[0165] Table 6

[0166] Modified particles Example Modification reagents Contact angle / ° <![CDATA[SiO2]]> 4 HDTMS 126.2 <![CDATA[Al2O3]]> 5 HDTMS 122.4 <![CDATA[Al2O3]]> 6 KH-560 119.5 <![CDATA[SiO2]]> 7 KH-560 118.6

[0167] Table 7

[0168]

[0169] Table 8

[0170]

[0171] Note: “ / ” represents no hydrophobicity.

[0172] Comparative Example 5

[0173] The particle size of SiO2 in Example 4 was adjusted to 50 nm, and the rest remained the same as in Example 1.

[0174] turn out:

[0175] The particles are very easy to agglomerate and cannot be evenly dispersed into the precursor solution at the same mass ratio of particles to precursor as in Example 4.

[0176] Comparative Example 6

[0177] The particle size of SiO2 in Example 4 was adjusted to 200 nm, and the rest remained the same as in Example 1.

[0178] turn out:

[0179] The particles are very easy to agglomerate and cannot be evenly dispersed into the precursor solution at the same mass ratio of particles to precursor as in Example 4.

[0180] Comparative Example 7

[0181] When the molar ratio of KH-792 to methyltrimethoxysilane in Example 1 is adjusted to 1.3:0.8, the other contents remain the same as in Example 1.

[0182] turn out:

[0183] When the molar ratio of KH-792 to methyltrimethoxysilane exceeds 1.2:0.8, the hydrophobicity of the synthesized amino-terminated hyperbranched siloxane is reduced due to excessive amino content; when the molar ratio of KH-792 to methyltrimethoxysilane is 1.3:0.8, the contact angle is 103.3°.

[0184] Comparative Example 8

[0185] In Example 1, when the molar ratio of KH-792 to methyltrimethoxysilane exceeds 1:1.5, the other conditions remain the same as those in Example 1.

[0186] turn out:

[0187] Gel is easily produced during the synthesis process.

[0188] Comparative Example 9

[0189] The modified particles prepared in Example 4 were prepared without adding tetraethyl orthosilicate, and the other steps were the same as in Example 4 to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

[0190] turn out:

[0191] The hydrophobic property decreased and the contact angle was 105.6°.

[0192] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing amino-terminated hyperbranched siloxane, characterized in that: The steps include: Mix KH-792, methoxytrimethylsilane, anhydrous ethanol and water in a molar ratio of 0.8-1.2:0.8-1.2:2.4-2.8:2, and perform a hydrolysis condensation reaction at 45-53°C for 20-40 minutes; Afterwards, the pH is adjusted to 1-3, and the reaction is continued at 55-60° C. and 350-550 rpm with stirring for 4-6 hours. The mixture is cooled, and by-products are removed to obtain a viscous liquid, namely, amino-terminated hyperbranched siloxane.

2. The amino-terminated hyperbranched siloxane prepared by the method according to claim 1.

3. A method for preparing a self-cleaning coating with a smooth surface, characterized in that: The steps include: The amino-terminated hyperbranched siloxane according to claim 2 is dispersed in anhydrous ethanol, and then ethylene glycol diglycidyl ether is added and mixed uniformly to obtain a uniform and transparent precursor; wherein the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in the ethylene glycol diglycidyl ether is 1:0-2; The precursor is then coated on a smooth surface, cross-linked and cured to obtain a self-cleaning coating.

4. The method according to claim 3, characterized in that The thickness of the self-cleaning coating on the smooth surface is 5-15μm.

5. A self-cleaning coating with a smooth surface prepared by the method of claim 3 or 4.

6. A method for preparing an amino-terminated hyperbranched polysiloxane-modified particle coating, characterized in that: The steps include: (1) Preparation of modified particles: Add nanoparticles into the ethanol solution and disperse them evenly to obtain component A; wherein the nanoparticles are one or two of SiO2 and Al2O3; Add a modifying agent, a cross-linking agent, and a catalyst into anhydrous ethanol and mix them evenly to obtain component B; wherein the modifying agent is one or two of KH560 and hexadecyltrimethoxysilane HDTMS; The components A and B are mixed and reacted, and after the reaction is completed, they are centrifuged and dried to obtain modified particles; (2) Preparation of amino-terminated hyperbranched polysiloxane-modified particle coating: The amino-terminated hyperbranched siloxane according to claim 2 is dispersed in anhydrous ethanol, and then ethylene glycol diglycidyl ether is added and mixed uniformly to obtain a uniform and transparent precursor; wherein the molar ratio of the amino group in the amino-terminated hyperbranched siloxane to the epoxy group in the ethylene glycol diglycidyl ether is 1:0.5-2; Afterwards, modified particles are added to the precursor to obtain a precursor containing the modified particles; Finally, the precursor containing the modified particles is coated on the smooth surface, cross-linked and cured to obtain an amino-terminated hyperbranched polysiloxane-modified particle coating.

7. The amino-terminated hyperbranched polysiloxane-modified particle coating prepared by the method of claim 6.

8. Application of the self-cleaning coating with smooth surface as claimed in claim 5, the amino-terminated hyperbranched siloxane as claimed in claim 2, and the amino-terminated hyperbranched polysiloxane-modified particle coating as claimed in claim 7 in the fields of automotive glass, architectural glass or solar photovoltaic glass.

9. A method for improving the mechanical stability and aging resistance of a smooth self-cleaning surface, characterized in that: The self-cleaning coating with a smooth surface as described in claim 5, the amino-terminated hyperbranched siloxane as described in claim 2, and the amino-terminated hyperbranched polysiloxane-modified particle coating as described in claim 7 are used.

10. A solar photovoltaic glass, characterized in that: The self-cleaning coating with a smooth surface as described in claim 5, the amino-terminated hyperbranched siloxane as described in claim 2, and the amino-terminated hyperbranched polysiloxane-modified particle coating as described in claim 7 are used.

Citation Information

Patent Citations

  • Preparation method of hyperbranched polysiloxane with controllable amino content

    CN102924722A

  • Preparation method of amino hyperbranched siloxane and modified polyimide aerogel material thereof

    CN116253882A

  • Flame-retardant matte polyester film

    CN117844198A

  • Hyperbranched polymers containing silicon atoms

    US6001945A